2021
DOI: 10.1155/2021/7331821
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuropeptides as Potential Crosstalks Linking Down Syndrome and Periodontitis Revealed by Transcriptomic Analyses

Abstract: Background. This bioinformatics study was aimed to investigate the relationship between periodontitis (PD) and Down Syndrome (DS) regarding potential crosstalk genes, related neuropeptides, and biological processes. Methods. Data for PD (GSE23586, GSE10334 and GSE16134) and DS (GSE35665) were downloaded from NCBI Gene Expression Omnibus (GEO). Following normalization and merging of PD data, differential expression analysis was performed ( p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…For PD, a bioinformatics study indicated that IGF2 was intersected between PD and Major depressive disorder (Sun et al, 2021). Another study also predicted that IGF2 was involved in genetic crosstalk between PD and Down Syndrome, indicating the importance of IGF2 in the pathogenesis of PD (Chen et al, 2021). IGF2 could suppress the proliferation and osteogenic differentiation of periodontal ligament cells (Konermann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For PD, a bioinformatics study indicated that IGF2 was intersected between PD and Major depressive disorder (Sun et al, 2021). Another study also predicted that IGF2 was involved in genetic crosstalk between PD and Down Syndrome, indicating the importance of IGF2 in the pathogenesis of PD (Chen et al, 2021). IGF2 could suppress the proliferation and osteogenic differentiation of periodontal ligament cells (Konermann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the genetic links between two related diseases is possible because of the advent of computational biology and the analytical approach. Several bioinformatics studies have attempted to identify the crosstalk genes that are deregulated in PC and PD [12][13][14][15][16][17]. The present research similarly aims to identify the m6A RNA methylation regulators linking PC and PD.…”
Section: Introductionmentioning
confidence: 96%
“…Some researchers suggest that immunological abnormalities detected in DS individuals such as T cell development, decreased specific antibody response to immunizations, and neuthrophil chemotaxis defects, make them more susceptible to infections including periodontitis 7,8 . Therefore, it has been implied that periodontal disease is more frequent and severe in DS individuals 9,10 . While there is a suggested link between these two conditions, individual study results have yielded inconclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Therefore, it has been implied that periodontal disease is more frequent and severe in DS individuals. 9,10 While there is a suggested link between these two conditions, individual study results have yielded inconclusive findings. Two studies, for example, found that the periodontal index and prevalence of periodontitis were not significantly different between DS and non-syndromic patients, despite a tendency for increased gingival inflammation severity in DS subjects.…”
mentioning
confidence: 99%